Penerapan Teori Penemuan Hukum dalam Putusan Hakim Pada Praktik Peradilan di Indonesia - Reviana Mutiara Indah; Suripno Marwanto; Azelia Rizki Sarwono; R. Rangga Maulana; Irwan Triadi (Journal of Law Perspectives Review, 2025)
This study examines the application of legal discovery theory in judicial decisions within the Indonesian judicial system. Judges in Indonesia are not only required to apply written law but also to interpret and construct legal norms when existing regulations are incomplete or insufficient. This condition creates a practical need for legal discovery as a means to fill legal gaps and ensure that judicial decisions reflect substantive justice. The objective of this paper is to analyze the theoretical foundations of legal discovery, explore how these theories operate within national legal principles, and identify how judges implement them in judicial reasoning. Using a normative juridical method, this study reviews statutory provisions, judicial decisions, and doctrinal sources to understand the patterns and rationale behind judicial legal discovery. The findings show that judges frequently rely on interpretation, legal principles, and societal values to establish legal norms, especially in cases involving regulatory ambiguity. These practices contribute to achieving justice and legal responsiveness, although they also pose challenges to maintaining legal certainty. The study concludes that legal discovery plays a strategic role in strengthening the judiciary’s function as a guardian of justice, and its proper application can enhance the adaptability of Indonesian law to evolving social needs.